Techno-economic assessment of stripping modifications in an ammonia-based post-combustion capture process - Li, K.; Yu, H.; Feron, P.; Wardhaugh, L.; Tade, Moses (Elsevier, 2016)
The energy penalty associated with solvent regeneration accounts for the largest part of overall energy consumption in aqueous ammonia (NH3)-based post-combustion capture (PCC) processes. While extensive research focus on the process improvements to reduce the energy burden of solvent regeneration, little attention has been paid to techno-economic assessments that analyse the related energy savings and capital costs. In the present study, we assessed the technical and economic benefits of stripping modifications in an NH3-based PCC process integrated into a coal-fired power station. The stripping configurations included a rich-split process, cold-rich bypass, inter-heating, and combinations of these processes. We used a rigorous, rate-based model in the Aspen Plus® RateSep simulator to determine the technical performance of these new process modifications, while capital investment was estimated with a cost model based on the Aspen Capital Cost Estimator (AACE). All the proposed stripper modifications have technical and economic advantages compared to the reference case. The best configuration was inter-heating integrated with the rich-split process, which reduced reboiler duty by 40.7% and saved 29.2% of annual costs. The sensitivity study suggests that the modified stripping processes can maintain the economic benefits over the wide variations of the important parameters.